Association of serum concentrations of persistent organic pollutants (POPs) and risk of pre-eclampsia: a case–control study. Issue 1 (December 2016) - Eslami, Bita; Malekafzali, Hossein; Rastkari, Noushin; Rashidi, Batool; Djazayeri, Abolghasem; Naddafi, Kazem
Abstract Background There is increasing evidence that persistent organic pollutants (POPs) may contribute to pre-eclampsia. The objective of this study was to evaluate the association between Polychlorinated Biphenyls (PCBs) and Polybrominated Diphenyl Ethers (PBDEs) as POPs with pre-eclampsia. Methods This case–control study was performed in the three general university hospitals of Tehran University of Medical Sciences. Serum samples were collected from cases (n = 45) who had diagnosed with preeclampsia and from control samples (n = 70) with normal pregnancy and attended the same hospital for a routine prenatal visit at the third trimester of pregnancy. Pollutants levels were analyzed by Gas Chromatography Mass Spectrometry (GC/MS). Results Mean participant age was 27.3 ± 5.39 with median 27. As the main independent variable, total POPs manifested with adjusted OR equal to 1.54 (95 % CI: 1.26–1.87, p -value <0.0001), which was significantly associated with pre-eclampsia. The adjusted OR proved a statistically significant association between total PCBs 1.77 (95 % CI: 1.34–2.32) and total PBDEs (OR = 2.19; 95 % CI: 1.39–3.45, p -value = 0.001) with pre-eclampsia considering confounding variables (maternal age, pre-pregnancy body mass index (BMI), gestational age, weight gain during pregnancy and total lipids in maternal serum). Finally, pre-pregnancy BMI and weight gain during pregnancy had a positive association with pre-eclampsia and gestational age yielded a negative association with pre-eclampsia in all analysis. Conclusion Our data indicate the association between total POPs, total PBDEs, and total PCBs with pre-eclampsia, even after controlling for the effects of a number of potentially confounding factors. Further investigation about route of exposure and the trend of POPs especially in pregnant women is needed.